2022
DOI: 10.1007/s11042-021-11863-3
|View full text |Cite
|
Sign up to set email alerts
|

On restoration of degraded fingerprints

Abstract: The state-of-the-art fingerprint matching systems achieve high accuracy on good quality fingerprints. However, degraded fingerprints obtained due to poor skin conditions of subjects or fingerprints obtained around a crime scene often have noisy background and poor ridge structure. Such degraded fingerprints pose problem for the existing fingerprint recognition systems. This paper presents a fingerprint restoration model for a poor quality fingerprint that reconstructs a binarized fingerprint image with an impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This GAN was applied iteratively to enhance the fingerprint image until its quality achieved a satisfying result. In 2022, Joshi et al [26] proposed a GAN with an attention mechanism called "CRGAN" by inserting channel refinement units in the generator and the discriminator to restore degraded fingerprints. Recently, in 2023, Zhu et al [27] developed a GAN framework called "FingerGAN," which generates a fingerprint skeleton image as the output instead of an enhanced fingerprint image.…”
Section: Spatial Domainmentioning
confidence: 99%
“…This GAN was applied iteratively to enhance the fingerprint image until its quality achieved a satisfying result. In 2022, Joshi et al [26] proposed a GAN with an attention mechanism called "CRGAN" by inserting channel refinement units in the generator and the discriminator to restore degraded fingerprints. Recently, in 2023, Zhu et al [27] developed a GAN framework called "FingerGAN," which generates a fingerprint skeleton image as the output instead of an enhanced fingerprint image.…”
Section: Spatial Domainmentioning
confidence: 99%
“…The generative adversial network (GAN) is the state-of-the-art image generation or enhancement techniques. The researchers in [ 112 ] recently demonstrated that the channel refinement-generative adversial network, which is one of the degraded fingerprint restoration methods, outperformed than the GAN and classical image processing enhancement.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…For instance, in pre-processing, standard quality estimation mechanism and state-of-the-art image enhancement techniques can be practiced, while in feature extraction, deep and invariant feature representation can be employed [ 126 ]. For instance, in image enhancement and restoration, generative adversial network, which is the state-of-the-art method for image generative problems [ 112 ], can be employed. For invariant feature representation, ridge orientation pattern can be used as it will not be affected by sensor differences [ 7 ].…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Fingerprints are among the most accurate and reliable biometric traits, which allows its applications in several domains, including digital transactions, criminal identification, and access control [3]- [7]. However, heavy noise is observed for fingerprints originating from a crime scene, commonly called latent fingerprints and fingerprints originating from individuals with poor skin condition around fingertips due to excessive manual work, such as fingerprints of the rural Indian population (see Figure 1).…”
Section: Introduction and Related Workmentioning
confidence: 99%